Development and validation of the self-talk questionnaire (S-TQ) for sports - Zervas, Y.a b; Stavrou, N.A.a; Psychountaki, M.a (Journal of Applied Sport Psychology, 2007)
The purpose of the present study was to describe the development and validation of the Self-Talk Questionnaire (S-TQ), designed to measure two functions of self-talk strategies, namely the motivational function and the cognitive function, used by athletes to enhance their sport performances. The study was conducted in three phases. The first phase targeted item selection and content relevance. The second phase set out to test the factor structure of the instrument. The aim of the third phase was focused on further examination of the psychometric properties of the instrument. The results of an exploratory factor analysis provided adequate support for the instrument. The S-TQ consists of 11 items, representing two factors (motivational and cognitive). A confirmatory factor analysis showed an acceptable fit to the data. The factors were internally consistent, the correlations with external criteria were significant, and test-retest reliability values were very good. Examining the relationships between the S-TQ and similar constructs supported convergent validity. Discriminant validity was supported by correlations between the S-TQ and a different construct. The S-TQ appears to be a promising psychometric instrument that can be used in research and psychological intervention programs.